Intergrasi Nilai Nilai Budaya Lokal Dalam Prespektif Hak Asasi Manusia Di Indonesia - Hendrikus Otniel Nasozaro Harefa; Yaman Adi Lahagu; Binal Amal Harefa; Keriyus Bu’ulolo; Onahia Waruwu; Ralex Sander Pratama Lase; Patrisius Fanuari Gulo; Marosokhi Zebua (Jurnal Ilmu Pendidikan Pancasila, Kewarganegaraan, dan Hukum, 2025)
This study aims to analyze the integration of local cultural values from a human rights perspective in Indonesia and to identify challenges and strategies in harmonizing local wisdom with universal human rights standards. Using qualitative research methods with a socio-legal approach, this study found that despite tensions between the universalism of human rights and cultural relativism, Indonesian local values such as mutual cooperation, deliberation, and communal rights have strong humanistic substance. The results of the study show that the integration of human rights will be more effective through the process of vernacularization, namely the translation of human rights principles into local languages and cultural symbols. The conclusion of this study confirms that local culture is not an obstacle to human rights, but rather an important instrument for strengthening the legitimacy and enforcement of human rights based on national identity. The need for stronger legal recognition of communal rights and the use of a cultural approach in conflict resolution are the main recommendations of this study.